LEGAL ANALYSIS OF KRATOM PLANT USE IN CENTRAL KALIMANTAN UNDER LAW NUMBER 35 OF 2009 ON NARCOTICS - Agnes Vania Chaterina Pratiwi; Ivans Januardy; Claudia Yuni Pramita; Fx. Ary Setiawan (SOSIOEDUKASI, 2026)
Kratom is an endemic plant originating from Southeast Asia that grows wild in Thailand, Malaysia, Vietnam, the Philippines, and Papua New Guinea. In Indonesia, this plant is predominantly found in Kalimantan. An examination of the legal underpinnings for the prohibition of kratom constitutes the primary objective of this study, alongside a determination of whether kratom warrants classification as a Schedule I narcotic. The research adopts a normative juridical methodology, operationalized through a statutory approach and substantiated by peer-reviewed scientific journals and authoritative instruments promulgated by competent institutions. The results indicate that, to date, there is no specific regulation governing kratom (Mitragyna speciosa) under Law Number 35 of 2009 on Narcotics; therefore, kratom has not been classified as a narcotic subject to criminal sanctions. The existing legal basis related to kratom remains limited to the Circular Letter of the Head of the National Agency of Drug and Food Control (BPOM) issued in 2016, which prohibits the use of kratom in traditional medicines and health supplements. The conclusion of this study is that the use of kratom in Central Kalimantan cannot yet be subjected to criminal provisions under Law Number 35 of 2009 on Narcotics, due to the absence of explicit regulation concerning kratom in the law and the fact that the existing legal framework is still limited to administrative policies issued by BPOM.